The windows of heaven - Cleeve, Roger (London : Davies, 1961)
Novel set in the 1800s; focuses on the brutality of the settlers way of life; cruelty towards and violent conflict with Aborigines.
Keywords: Race relations - Violent; Literature and stories - Non indigenous - Fiction; Southwest New South Wales (SW NSW SI54, SI55)